MicroRNA-132 Interact with p250GAP/Cdc42 Pathway in the Hippocampal Neuronal Culture Model of Acquired Epilepsy and Associated with Epileptogenesis Process - Jinxian Yuan; Hao Huang; Xin Zhou; Xi Liu; Shu Ou; Tao Xu; Ruohan Li; Limin Ma; Yangmei Chen (Neural Plasticity)
Increasing evidence suggests that epilepsy is the result of synaptic reorganization and pathological excitatory loop formation in the central nervous system; however, the mechanisms that regulate this process are not well understood. We proposed that microRNA-132 (miR-132) and p250GAP might play important roles in this process by activating the downstream Rho GTPase family. We tested this hypothesis using a magnesium-free medium-induced epileptic model of cultured hippocampal neurons. We investigated whether miR-132 regulates GTPase activity through p250GAP and found that Cdc42 was significantly activated in our experimental model. Silencing miR-132 inhibited the electrical excitability level of cultured epileptic neurons, whereas silencing p250GAP had an opposite effect. In addition, we verified the effect of miR-132 in vivo and found that silencing miR-132 inhibited the aberrant formation of dendritic spines and chronic spontaneous seizure in a lithium-pilocarpine-induced epileptic mouse model. Finally, we confirmed that silencing miR-132 has a neuroprotective effect on cultured epileptic neurons; however, this effect did not occur through the p250GAP pathway. Generally, silencing miR-132 may suppress spontaneous seizure activity through the miR-132/p250GAP/Cdc42 pathway by regulating the morphology and electrophysiology of dendritic spines; therefore, miR-132 may serve as a potential target for the development of antiepileptic drugs.